2010
DOI: 10.1007/s10295-010-0725-6
|View full text |Cite
|
Sign up to set email alerts
|

A highly thermostable antimicrobial peptide from Aspergillus clavatus ES1: biochemical and molecular characterization

Abstract: Antimicrobial peptides (AMPs) are extremely attractive candidates as therapeutic agents due to their wide spectrum of antimicrobial activity and mechanism of action, which differs from that of small-molecule antibiotics. In this study, a 6.0-kDa antimicrobial peptide from Aspergillus clavatus ES1, designated as AcAMP, was isolated by a one-step heat treatment. AcAMP was sensitive to proteolytic enzymes, stable between pH 5.0 and 10.0, and heat resistant (15 min at 100 degrees C). The acamp gene encoding AcAMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 28 publications
(43 reference statements)
0
25
0
Order By: Relevance
“…Other antifungal proteins produced by ascomycetes are PAF from P. chrysogenum Q176 (Marx et al 1995), PcArctin from P. chrysogenum A096 (Chen et al 2013), BP from Penicillium brevicompactum (Seibold et al 2011), AFP and AFP NN5353 from Aspergillus giganteus (Nakaya et al 1990;Binder et al 2011), Anafp from Aspergillus niger (Gun , AcAFP and AcAMP from Aspergillus clavatus (Skouri-Gargouri and Gargouri 2008; Hajji et al 2010), FPAP from Fusarium polyphialidicum (Galgóczy et al 2013b), and NFAP from Neosartorya fischeri (Kovács et al 2011). Mechanisms of action of antifungal proteins from molds have been described as multifactorial, where membrane permeabilization, changes in actin distribution, chitin biosynthesis inhibition, destabilization of cell wall, Electronic supplementary material The online version of this article (doi:10.1007/s00253-015-7020-4) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Other antifungal proteins produced by ascomycetes are PAF from P. chrysogenum Q176 (Marx et al 1995), PcArctin from P. chrysogenum A096 (Chen et al 2013), BP from Penicillium brevicompactum (Seibold et al 2011), AFP and AFP NN5353 from Aspergillus giganteus (Nakaya et al 1990;Binder et al 2011), Anafp from Aspergillus niger (Gun , AcAFP and AcAMP from Aspergillus clavatus (Skouri-Gargouri and Gargouri 2008; Hajji et al 2010), FPAP from Fusarium polyphialidicum (Galgóczy et al 2013b), and NFAP from Neosartorya fischeri (Kovács et al 2011). Mechanisms of action of antifungal proteins from molds have been described as multifactorial, where membrane permeabilization, changes in actin distribution, chitin biosynthesis inhibition, destabilization of cell wall, Electronic supplementary material The online version of this article (doi:10.1007/s00253-015-7020-4) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…From the second part of the 1990s, three low-molecularmass, basic, cysteine-rich, extracellular antifungal proteins with highly similar structure to b-defensins have been isolated and characterized from fungal isolates belonging to the genus Aspergillus: Aspergillus giganteus (Aspergillus giganteus antifungal protein; AFP), Aspergillus clavatus (Aspergillus clavatus antifungal protein; AcAMP) and Aspergillus niger (Aspergillus niger antifungal protein; ANAFP) (Meyer, 2008;Hajji et al, 2010). In our previous work we demonstrated that the Neosartorya fischeri (anamorph: Aspergillus fischerianus) NRRL 181 isolate also secretes a similar protein, the Neosartorya fischeri antifungal protein (NFAP) (Kovács et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…It is 6.0 kDa and shows characteristics common to the group of small, basic, cysteine-rich antifungal proteins from molds. 71 It is also pH tolerant and active against bacteria and fungi. The open-reading frame is of 282 bp encoding a peptide of 94 amino-acid residues consisting of a 21-amino-acid signal peptide, a 22-amino-acid pro-peptide and a 51-amino-acid mature peptide.…”
Section: Sources Of Ribosomally Synthesized Antimicrobial Peptides Bamentioning
confidence: 99%